Conductivity Enhancement of Nickel Oxide by Copper Cation Codoping for Hybrid Organic-Inorganic Light-Emitting Diodes - Kim, Moohyun; Joo, Chul Woong; Kim, Jong H.; Choi, Wonseok; Lee, Jonghee; Lee, Dongchan; Cho, Hyunsu; Lee, Hyunkoo; Park, Sunjoong; Cho, Nam Sung; Cho, Hyunjin; Lee, Chan Woo; et al. (ACS Photonics, 2018)
We demonstrate a Cu(I) and Cu(II) codoped nickel(II) oxide (NiOx) hole injection layer (HIL) for solution-processed hybrid organic-inorganic light-emitting diodes (HyLEDs). Codoped NiOx films show no degradation on optical properties in the visible range (400-700 nm) but have enhanced electrical properties compared to those of conventional Cu(II)-only doped NiOx film. Codoped NiOx film shows an over four times increased vertical current in comparison with that of NiOx in conductive atomic force microscopy (c-AFM) configuration. Moreover, the hole injection ability of codoped NiOx is also improved, which has ionization energy of 5.45 eV, 0.14 eV higher than the value of NiOx film. These improvements are a consequence of surface chemical composition change in NiOx due to Cu cation codoping. More off-stoichiometric NiOx formed by codoping includes a large amount of Ni vacancies, which lead to better electrical properties. Density functional theory calculations also show that Cu doped NiO model structure with Ni vacancy contains diverse oxidation states of Ni based on both density of states and partial atomic charge analysis. Finally, HyLEDs of Cu codoped NiOx HIL have higher performance comparing with those of pristine NiOx. The current efficiency of devices with NiOx and codoped NiOx HIL are 11.2 and 15.4 cd/A, respectively. Therefore, codoped NiOx is applicable to various optoelectronic devices due to simple sol-gel process and enhanced doping efficiency.
Keywords: Conductive atomic force microscopy; Conductivity enhancement; Current efficiency; Doping efficiency; Hole injection layers; Hybrid organic-inorganic; Solution-processed; Surface chemical composition; codoping; hole injection layer; Nickel(II) oxide; sol-gel processed